Pregnancy outcome in a bicornuate uterus with bilateral pregnancy presenting as threatened abortion: a case report - Acharyya, Tanaya; Gohain, Bandana Shyam; Morang, Kripanath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Congenital uterine anomalies or mullerian anomalies are prevalent in 0.4 to 10% of women in general and are often manifested by reproductive challenges like miscarriage, premature labor, premature rupture of membranes or malpresentation. Having a bilateral pregnancy in a bicornuate uterus is extremely rare, especially if it is a spontaneous conception.